PERAN KONEKSI POLITIK TERHADAP HUBUNGAN PENJUALAN KEPADA PIHAK BERELASI DENGAN NILAI PERUSAHAAN - M.J, Ermad; Rusnaidi, Rusnaidi; Umar, Zulkifli; Ajeng Savitri, Dini (Berajah Journal, 2024)
This study aims to examine the role of political connections in the relationship between related party sales and firm values. The population of the study consists of non-financial companies listed on the Indonesia Stock Exchange from 2020 to 2023, totaling 2,309 companies. A sample of 74 companies, with 296 observations, was selected based on specific criteria. The data analysis method used is ordinary least square. The study finds that related party sales negatively impact firm value. Moreover, this negative impact is more pronounced in companies with political connections. These findings indicate that companies engaged in related party sales tend to experience a decrease in firm value, and political connections exacerbate this decline. Therefore, it is crucial for companies to consider the impact of political connections in related party sales activities to optimize firm value.